Engineered Electrode Structure for High‐Performance 3D‐Printed All‐Solid‐State Flexible Microsupercapacitors. Issue 7 (19th May 2021) - Zhang, Yan; Wang, Yaling; Ganesh, Anandha; Wang, Guolong; Shi, Xiaowei; Qiao, Yide; Liu, Jiamei; Liu, Heguang; Li, Lei
Abstract : Graphene aggregation is the major issue limiting its electrochemical performance when used as electrode material for microsupercapacitors (MSCs) with the interdigitated architecture. Solving this issue boosts the device's electrochemical performance, especially the areal energy density, facilitating its applications in advanced miniaturized electronic systems. Herein, a facile method to prepare the graphene−carbon black composite ink for the direct 3D printing of electrodes of MSCs is developed. Carbon black present in the composite ink tailors the graphene sheets space in the electrode structure during the 3D printing process, relieving the graphene aggregation issue. The MSCs show great improved electrochemical performance with a high areal energy density (2.49 μWh cm −2 ), high power density (0.25 mW cm −2 ), promising cycling stability, and good mechanical flexibility. The method developed herein paves a way to prepare high‐performance, all‐solid‐state flexible MSCs in a scalable process. Abstract : The solution‐processed graphene−carbon black composite ink is developed for the scalable printing of all‐solid‐state flexible microsupercapacitor devices. The devices demonstrate high areal capacitance, high areal energy density and power density, and good cycling stability with excellent mechanical flexibility.